But I dońt want to be a movie star - Pinder, Margaret (London : Walker Books, 2006)
While spending the summer in California with her movie-star grandmother, fifteen-year-old Kat reluctantly agrees to impersonate the aging actress in the hopes of helping her land an important movie role.
Keywords: Actor and actrist -- Fiction; California -- Fiction; Grandmothers -- Fiction